Antibiogram Of Bacteria And Fungal Isolates Associated With Otitis Media Amongst Children In Bauchi State, Nigeria - BELLO, R. H,; AGBO, E.B,; OLABODE, H.O.K, (International Journal of Pharma and Bio Sciences, 2011)
A total of 400 ear swabs were collected from infant and children within the ages of 0-12years. All samples were cultured on MCA, BA, CA, and SDA plates which yielded the following Staphylococcus aureus, Proteus mirabilis, Escherichia coli, Pseudomonas aeruginosa Streptococcus species, Klebssiella spp, and Candida albicans. These bacteria isolates were tested against selected antibiotics such as Tetracycline, Gentamycin, Ampiclox, Chloramphenicol, Augmentin, Enthromycin, Cotrimoxazole and Ciprfloxacin, using Disc diffusion method. Ciprofloxcin was the most sensitive antibiotic with Tetracycline and Chloramphenicol being the least. The isolate antibiotic susceptibility was statistically significant by ANOVA (P<0.05) which on further analysis with LSD and DMRT revealed that Ciprfloxacin isolate sensitivity was significantly different to all the antibiotics while Gentamycin was statistically significant over Tetracycline, Chloramphenicol and Cotrimoxazole. Furthermore, an overall assessment of 75.43% sensitivity and 24.57% resistance respectively was observed which was statistically significant by Chi square (P< 0.05) analysis. Isolates of C. albicans were tested against selected orally administer antifungal agents such as Fluconazole, Ketoconazole, Griseofulvin and Terbinafine using Microdilution tube method. Terbinafine was the most sensitive and Fluconazole was the least. This study concludes that Ciprofloxcin and Terbinafine are the most effective drugs of choice in first line treatment of Otitis media in children. Hence, for effective management of cases a preceding mycology investigation should supplement bacteriological diagnostic procedures.